Mother’s Love beyond the Mask: Resilience of Covid-19 Mother Survivors in Indonesia - Putri Nabhani Nurany; Rosleny Marliani; Anizar Rahayu (LPPM IAIN Parepare, 2021)
The curve of Covid-19 in Indonesia has not sloped, the positive number of this virus continues to increase. One groups affected Covid-19 are working mothers who have babies and still need to feed and take care for the babies. The positive status of Covid-19 for these mothers is certainly not easy because it has its own dynamics. They got anxiety about their health and safety as well as the babies. It is aggravated by anxiety of self-isolation so they are forced to be separated from their family and relatives. This study aims to understand a unique case in depth so that the methodology used is a case study. The data obtained through interviews with one subject, a mother who has survived Covid-19. The research data were analyzed by data reduction stages, by making verbatim and then making exploratory comments. From these exploratory comments the data then developed into emergent themes which will then be reduced and grouped under super-ordinate themes. The results of the study describe eight themes, namely: (1) Dark phase, (2) Closure, (3) Coping strategies, (4) Refocusing and Move on, (5) Adaptable, (6) Social Support, (7) Spirituality, and (8) Self Regard. This study found that during self-isolation, participant succeeded in developing her resilience in facing difficult times.